Markers of chronic hepatitis B at patients with HIV-infection and treatment approaches - S. I. Maksimov; S. P. Tsarenko; A. V. Kravchenko; N. Yu. Gankina; N. D. Yushchuk (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Assessment of prevalence of markers of the on-going, transferred or «concealed» CHB-infection at patients with HIV-infection in Moscow and in several regions of the Russian Federation.Material and methods. In Moscow and in several regions of the Russian Federations analysis of questionnaires of 340 228 patients with HIV-infection staying at dispensary observation at 80 territorial centers of AIDS and infectious diseases prophylaxis has been carried out. The blood samples obtained from 2 754 HIV-infected patients from 8 regions of the Russian Federations and from 240 patients with HIV-infection, observed in Moskovsk city AIDS center were studied. Analysis of the out-patient records of 16 813 patients, observed at this center was carried out. All blood samples were investigated for the presence of НBV, HDV, HCV, HAV-virus markers in serum by enzyme-linked immunoassay and for the presence of RNA HIV, RNA HCV and DNA HBV by polymerase chain reaction.Results. It was revealed, that CHB markers are detected approximately at 5,5–6,8% of patients with HIV-infection, in most of the cases in combination to CHC or CHD markers. Significant part (25%) of HBsAgpositive HIV-infected inhabitants of Krasnoyarsk region have hepatitis D markers. Frequency of «hidden» CHBinfection at HIV-infected patients was 8,8% in Moscow and 44,4 % – in Krasnoyarsk region. Conclusion. It is recommended to determine markers of transferred CHB-infection at HIV-infected patients and their presence to test blood for HBV DNA. Observation of patients with combined CHB/HIV infection, not requiring in antiretroviral treatment and CHBs receiving telbivudine treatment, revealed effective suppression of HBV replication and did not influence HIV viral load.